2004
DOI: 10.1038/sj.bjc.6601767
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C and NF-κB in proteolysis-inducing factor-induced proteasome expression in C2C12 myotubes

Abstract: Proteolysis-inducing factor (PIF) is a sulphated glycoprotein produced by cachexia-inducing tumours, which initiates muscle protein degradation through an increased expression of the ubiquitin -proteasome proteolytic pathway. The role of kinase C (PKC) in PIFinduced proteasome expression has been studied in murine myotubes as a surrogate model of skeletal muscle. Proteasome expression induced by PIF was attenuated by 4a-phorbol 12-myristate 13-acetate (100 nM) and by the PKC inhibitors Ro31-8220 (10 mM), staur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 34 publications
1
32
0
4
Order By: Relevance
“…The former causes the release of arachidonic acid from membrane phospholipids, while diacylglycerol, derived from PC-PLC, has been suggested to provide a positive feedback signal to protein kinase C (PKC) . We have shown PKC to be involved in PIF-induced proteasome expression (Smith et al, 2004) and PKC may act as a signal for NF-kB activation through phosphorylation and activation of IKK (Fullman et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former causes the release of arachidonic acid from membrane phospholipids, while diacylglycerol, derived from PC-PLC, has been suggested to provide a positive feedback signal to protein kinase C (PKC) . We have shown PKC to be involved in PIF-induced proteasome expression (Smith et al, 2004) and PKC may act as a signal for NF-kB activation through phosphorylation and activation of IKK (Fullman et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Stable transfections were carried out on cells at 50 -80% confluency using GeneJuice, according to the manufacturer's protocol, and selected by resistance to ampicillin (5 g l À1 ) as described previously (Smith et al, 2004). Transfected myoblasts were stimulated to differentiate by replacing the growth medium with DMEM supplemented with 2% HS, when the cells reached confluence.…”
Section: Myogenic Cell Culture and Transfectionmentioning
confidence: 99%
“…Other signalling pathways activated by PIF and leading to protein degradation including activation of protein kinase C (PKC) (Fig. 5A) [20], formation of ROS (Fig. 5B) [18], and nuclear accumulation of NF-B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown a role for protein kinase C (PKC) in the induction of proteasome expression by both PIF (43) and Ang II (8). A key step in protein degradation by both PIF and Ang II is the transient formation of reactive oxygen species, possibly through activation of NADPH oxidase by arachidonate and PKC.…”
Section: Discussionmentioning
confidence: 99%